International Education System in Pedagogical Studies - Indri Pangastuti; Yaya Sunarya (al-Afkar, Journal For Islamic Studies, 2025)
The Team of the Directorate of the Educator Profession, Directorate General for Improving the Quality of Educators and Education Personnel (2006) has substantively formulated pedagogical competencies which include the ability to understand students, design and implement learning, evaluate learning outcomes, and develop students to actualize the various potentials they have. Education is "a conscious and planned effort to create a pleasant learning and learning atmosphere so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves and society." The curriculum of international education systems has a broader focus on global abilities and skills. Career paths and international educational studies reach an international level. The research method used in this research is the literature review method or literature study. This method examines sources containing theories that are in accordance with research problems, especially from writings or articles published in various scientific journals that are in accordance with the study in this research. . Understanding the concept of education will have an impact on how teachers apply theory to practice, how teachers interpret the teaching and learning process in the classroom, how teachers respond to many and routine tasks that are not always accompanied by economic value, how teachers want to encourage children to learn. continuously, and how teachers can create educational innovations based on their teaching experiences.